The impact of watershed hydrology on landscape development - Naim Shauqi , Mohd Noor (2015)
Nowadays, numbers of study have been made to the soil or the impact of geomorphology on the hydrological process of stream flow such as sea, river and others, but much less concentration that have given to the opposite which is the impact and effect of hydrological process on the evolution of stream flow topography. Therefore, the study of changes of geomorphology is important to the development of our country. The problem is rises when the landscape development analysis and modeling Is neglected when there are extremely natural disasters happen but in silent the impact or effect on the deposition on the river bed can be important particularly when threshold are involved in the development. To determine the process of runoff, the area of sediment should be analyze so that the area of watershed and flow rate is suitable and does not give effect to the surrounding. The main objective of this study was to validate the changes of sediment or river bed is according to the flow rate of the stream flow. The specific objectives as follows; To establish the time series of river changes maps using Arc GIS, and to analyse the relationship of hydrological process (i.e. flow of stream) to the river changes. In this study, the stream and sediments location of the study area for the last four years were obtained from Google Earth image. The flow rate of stream flow of study area (Sungai Kuantan, Bukit Kenau, Kuantan, Pahang) obtained from the Jabatan Pengairan dan Saliran Malaysia (JPS). The flow rate were analysed based on the minimum, maximum and mean of flow rate of the year. The sediment area values changes derived from the Arc GIS show a relationship to the maximum, minimum and mean of the flow rate. From this relationship, arithmetic equation could be derived as 0.0000789Q for the relation between the flow rate and the changes of the sediment area values which is the Q is the flow rate of the stream flow. Therefore, the flow rate could affect the changes in the area of sediment.